Recent trends in incidence, geographical distribution, and survival of papillary thyroid cancer in France. Issue 4 (August 2015) - Colonna, M.; Uhry, Z.; Guizard, AV.; Delafosse, P.; Schvartz, C.; Belot, A.; Grosclaude, P.; ,
Highlights: Time trend analysis of papillary thyroid cancer showed a dramatic increase. This increase has slowed down within in recent years, especially at younger ages. There is a strong geographic disparity in incidence between areas in France. 10-years net survival is high and has improved between 1989 and 2004. Abstract: Background: Over the past few decades, the incidence of thyroid cancer has dramatically increased in many countries. This increase was mainly seen in papillary cancer. The role of diagnostic practices and the effects of other risk factors were suggested to explain this increase. We provide a descriptive analysis in terms of changes in incidence, geographical distribution, and survival to check the relevance of assumptions about the increase. Methods: A detailed analysis of changes in incidence recorded in French cancer registries between 1982 and 2010 was performed taking into account age, period, and birth cohort. The geographical distribution of the incidence in the 2006–2010 period was estimated from the standardized incidence ratios. The net survival was estimated to evaluate the effects of sex, age, and period of diagnosis in patients diagnosed between 1989 and 2004 and followed-up until 2013. Results: The incidence of papillary cancer has increased sharply over the 1982–2010 period; the average annual rate of increase was 7.8% in men and 7.2% in women. The increase has slowed in the recent period in people aged less than 50 at the time of diagnosis. It has also slowed in the cohorts born 1945 and after. There was a strong geographic disparity in incidence between areas covered by cancer registries. Finally, the net survival was very high; the 10-year net survival was 96% and improved progressively from 82% in patients diagnosed between 1989 and 1993 to 95% in those diagnosed between 1999 and 2004. Conclusion: The increased incidence results most probably from the effect of medical practice, although other risk factors seem also involved, but to a lesser extent. The increase seems to have slowed down in the recent years, especially in the youngest age groups. This observation suggests a recent trend towards saturation of the effects of medical practices in post-1945 cohorts associated with an effect of the gradual dissemination of the recommendations relative to the management of thyroid nodules.